Developing a Comprehensive Library Marketing Strategy for Effective Outreach - Sonal Umesh patil; Amita Sharma (MultiTech Publisher, 2021)
The promotion and marketing of the library and information sector is necessary in academic environments such as universities and colleges in order to raise awareness of the library services. Product marketing is crucial for businesses in order to improve sales and, ultimately, profit. The idea of promoting libraries and marketing library services is discussed in this essay. The collections of academic libraries are diverse. Marketing library products is essential to promoting the active collection. In this essay, methods and strategies for effectively marketing library services are suggested